Strategi Pemberian Layanan Wirausaha Dessertbox untuk Meningkatkan Jiwa Kemandirian Remaja di Era Milenial - Feby Annisa, Salwa; Hartanto, Doddy; Setyowati, Aprilia (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The quasi-experimental method of providing entrepreneurial services is a strategy for developing the level of independence of teenagers in the millennium era. Currently, the strategy is being implemented to develop the entrepreneurial spirit of teenagers which aims to provide opportunities to become young entrepreneurs. In the current millennial era, there are many opportunities to earn income through independent entrepreneurship. This entrepreneurial service is provided to millennial teenagers not only to foster a spirit of independence but also to shape teenagers' creativity in entrepreneurship. Providing entrepreneurial services to teenagers in the current millennial era is very influential for the future, such as when teenagers are still studying at university, by providing entrepreneurial services it is able to foster the creative spirit of teenagers in creating small businesses that can generate financial coffers.